2019
DOI: 10.1002/qj.3534
|View full text |Cite
|
Sign up to set email alerts
|

On the properties of ensemble forecast sensitivity to observations

Abstract: Evaluating impacts of observations on the skill of numerical weather prediction (NWP) is important. The Ensemble Forecast Sensitivity to Observation (EFSO) provides an efficient approach to diagnosing observation impacts, quantifying how much each observation improves or degrades a subsequent forecast with a given verification reference. This study investigates the sensitivity of EFSO impact estimates to the choice of the verification reference, using a global NWP system consisting of the Non‐hydrostatic Icosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…(2018) and Kotsuki et al . (2019) have found that biases can have large effects when calculating FSO. The GMAO OSSE is not completely devoid of bias—there are some model biases that result from differences in model physics between the G5NR and the forecast model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2018) and Kotsuki et al . (2019) have found that biases can have large effects when calculating FSO. The GMAO OSSE is not completely devoid of bias—there are some model biases that result from differences in model physics between the G5NR and the forecast model.…”
Section: Discussionmentioning
confidence: 99%
“…(2013) and Kotsuki et al . (2019) found higher fractions of beneficial observations, as much as 60–70%, for 6‐hr forecasts. The expectation is that, as the forecast length increases and the error growth reaches saturation, the fraction of beneficial observations will approach 0.50, as any individual observation may be considered to perturb the long‐term forecast field randomly.…”
Section: Evolution Of Adjoint Impactsmentioning
confidence: 97%
See 1 more Smart Citation
“…The advection of the localization center (Ota et al 2013) is not applied. The EFSO impact estimates were not very sensitive to the choice of the RTPS parameter in the NICAM-LETKF (Kotsuki et al 2018b).…”
Section: Nicam-letkfmentioning
confidence: 95%
“…For this purpose, we use a data assimilation (DA) system comprising the Nonhydrostatic ICosahedral Atmospheric Model (NICAM; Satoh et al 2008Satoh et al , 2014 and the Local Ensemble Transform Kalman Filter (LETKF; Hunt et al 2007). The NICAM-LETKF system was developed by Terasaki et al (2015) and has been extended continuously to assimilate satellite radiance and precipitation data (Terasaki and Miyoshi 2017;Kotsuki et al 2017a), to estimate model parameters (Kotsuki et al 2018a), to improve its variance inflation method (Kotsuki et al 2017b), to diagnose assimilated observations (Kotsuki et al 2018b), and to accelerate its computation for high-performance computing systems (Yashiro et al 2016). Recently, a 100-member near-real-time NICAM-LETKF system started running on the Japan Aerospace eXploration Agency (JAXA)'s second-generation supercomputer system (JSS2).…”
Section: Introductionmentioning
confidence: 99%